Correction of Central Diastema and Individual Dental Malposition with Removable Orthodontic Appliance - Bayu Ananda Paryontri (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2023)
Background: Central diastema refers to an anterior spacing between maxillary central incisors and malposition of the individual teeth refers to the teeth being crowded in the upper and lower jaws. There are many causative factors that contribute to the occurrence of these two cases, such as heredity, frenulum deformity, gender, and bad habit. Removable orthodontic appliances are devices that can be used in cases of mild malocclusion. Objective: The purpose of writing this case report is to show that removable orthodontic appliances are the first choice for dentists. Case: A 23-year-old male patient came to UMY Dental and Oral Hospital (RSGM UMY) complaining that his front teeth had spacing and some irregularly arranged teeth. The patient felt uncomfortable with the condition of the teeth. Patient complaints are felt as early as 3 years ago. One year ago, had already used a removable orthodontic appliance and after the treatment is finished then used a retainer but only for 1 month because the retainer is missing. The case of this patient is class I Angle with central diastema and malposition of individual teeth. Case Management: Treatment is carried out using removable orthodontic appliances. The appliances component uses a simple spring on tooth 31 and 41, retentive component uses Adam’s clasp on teeth 16, 26, 36 and 46. Labial arch with a U loop in between canine and first premolar. Conclusion: The removable orthodontic appliance should be used to correct cases of mild malocclusion such as a central diastema with mild malposition of the individual teeth.